2020
DOI: 10.1371/journal.pone.0227405
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of psychopathy and khat abuse among prisoners in the correctional institution in Jimma, Ethiopia

Abstract: Background Khat abuse and psychopathy are both strongly related to criminal activity. Higher rates of substance use in people with psychopathy are hypothesized to be related to psychopathic personality traits, which include high sensation seeking, low conscientiousness and neuroticism, impulsivity, and irresponsibility. Little is known, however, about the association between psychopathy and khat abuse among prisoners in Ethiopia. Therefore, we evaluated the presence of these two factors in prisoners in the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 17 publications
(18 reference statements)
0
10
0
4
Order By: Relevance
“…This study found that around one-third (28.5%) of the prisoners in Debre Berhan prison had PKU, before imprisonment. This is less than a prevalence reported from Jimm Prison studies which found that 44% and 60% of prisoners use Khat [8,50]. The difference is probably due to one of those studies used of different instruments was conducted only among homicide offenders [8].…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…This study found that around one-third (28.5%) of the prisoners in Debre Berhan prison had PKU, before imprisonment. This is less than a prevalence reported from Jimm Prison studies which found that 44% and 60% of prisoners use Khat [8,50]. The difference is probably due to one of those studies used of different instruments was conducted only among homicide offenders [8].…”
Section: Discussionmentioning
confidence: 85%
“…DAST-20 is easy to administer and has been used in diverse populations. We used DAST in our study because, there is no measure developed or adapted for assessing PKU, and previous published studies in Ethiopia used DAST to measure problematic khat use [50,54].…”
Section: Assessment Of Problematic Khat Usementioning
confidence: 99%
See 2 more Smart Citations
“…29,30 The data presented in this paper were obtained from the study on psychopathy and associated factors among newly admitted prisoners in a correctional institution located in Bench Shako and West Omo zone correctional institution, Mizan Aman, Ethiopia. 27 Even though substance use disorder, association between alcohol and trauma, association between psychopathy and khat abuse, and psychopathy and associated factors among prisoners in Ethiopia were well established [31][32][33][34] up to date, the potential association between post-traumatic stress disorder and trauma exposure with problematic khat use among prisoners has not been investigated in our country Ethiopia, or elsewhere. Therefore, the aim of this study was to assess the association between life time trauma exposure and post-traumatic stress disorder with khat use disorder among newlyadmitted prisoners in Bench Shako and West Omo zone correctional institution, Mizan Aman, Ethiopia.…”
Section: Introductionmentioning
confidence: 97%